Everybody Is Doing It In Paso Robles, Cal.: They Waste No Time! [front and back]
A man and woman hugging to the right and the phrase 'Everybody Is Doing It In Paso Robles, Cal.: They Lose No Time!' with a blue pennant to the left. Back of postcard reads: 'Paso Robles. D[illeg.] Friend Doe, No Heidleberg Push cards here. Out with a gun all day. Best [illeg.] [illeg.]' Addressed to 'Dr. N.J. Gunn, 22nd & Bryant St., San Francisco, Calif.'